A novel detection method of Cryptosporidium parvum infection in cattle based on Cryptosporidium parvum virus 1. (13th December 2018) - Tai, Lixin; Li, Jianhua; Yin, Jigang; Zhang, Nan; Yang, Ju; Li, He; Yang, Zhengtao; Gong, Pengtao; Zhang, Xichen
Abstract: Cryptosporidium parvum is an important zoonotic parasite that causes significant economic loss in the animal husbandry industry, especially the cattle industry. As there is no specific vaccine or drug against Cryptosporidium, a rapid and accurate method for the detection of C . parvum is of great significance. In this study, colloidal gold strips were developed based on Cryptosporidium parvum virus 1 (CSpV1) for the detection of C. parvum infection in cattle fecal samples. The colloidal gold solution was prepared by reducing trisodium citrate and the CSpV1 #5 monoclonal antibody was labeled with colloidal gold. A polyclonal antibody against the CSpV1 capsid protein and an anti-mouse IgG antibody were coated on the colloidal gold strips for use in the test and control lines, respectively. Our results showed that the detection sensitivity in fecal samples was up to a 1:64 dilution. There was no cross-reaction with Cryptosporidium andersoni or Giardia in the fecal samples. The different preservation conditions (room temperature, 4°C, and 37°C) and preservation time (7, 30, 60, and 90 days) were analyzed. The data showed that the strips could be preserved for 90 days at 4°C and for 60 days at room temperature or 37°C. The colloidal gold strips were used to detect the samples of 120 clinical fecal in Changchun, China. The results indicated that the rate of a positive test was 5% (6/120). This study provides a rapid and accurate method for detecting C. parvum infection in cattle and humans.